Complexity and security - Ramsden, Jeremy; Kervalishvili, Paata J. (NATO science for peace and security series. Human and societal dynamics, 2008)
Develops a fundamental concept that in order to achieve security in a complex world, it is essential to ensure that we have sufficient variety available to cope with complexity and its potential dangers. This book develops many facets of this idea, covering major world issues, including energy, food and environmental security, and climate change.